Analysis of Phonological Errors in Fruit Buyers at Karangpucung Market - Renovriska, Melia Dwi; Darmawan, Almas Rifqi; Afifah, Hana (Journal of Language, Literature and Teaching, 2024)
The main purpose of this study is to investigate mistakes in phonology. Phonology is the aspect of language concerned with the sound system that is produced by human speech organs. Mistakes in phonology take place when words spoken by the speaking tools do not correspond to their intended pronunciation, thus affecting the diversity of oral and written forms of a language. Specific errors encompass phoneme deletion and addition. Therefore, there is a necessity for error analysis in language so as to recognize and assess them for useful teaching and learning techniques in schools. The data used in this research consists of errors made at the phonological level which were observed among fruit buyers at Karangpucung market while source data refers to utterances made by these participants in this market. Consequently, this study employs a qualitative descriptive design, listening to conversations containing phonological errors using note-taking to record these language errors at the said level.Keywords: Language, Phonology, Error Analysis